2016
DOI: 10.1136/bmjdrc-2015-000186
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in prediabetes and diabetes in the Suriname Health Study

Abstract: BackgroundDiabetes is increasing worldwide, and information on risk factors to develop targeted interventions is limited. Therefore, we analyzed data of the Suriname Health Study to estimate the prevalence of prediabetes and diabetes. We also explored whether ethnic differences in prediabetes or diabetes risk could be explained by biological, demographic, lifestyle, anthropometric, and metabolic risk factors.MethodThe study was designed according to the WHO Steps guidelines. Fasting blood glucose levels were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…The higher prevalences, found among the Amerindians, Hindustanis and Javanese, are in line with published findings on MetS components from the Suriname Health Study 19. These findings also concur with the higher prevalences reported in the Mexicans and Hispanics in the USA 33…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The higher prevalences, found among the Amerindians, Hindustanis and Javanese, are in line with published findings on MetS components from the Suriname Health Study 19. These findings also concur with the higher prevalences reported in the Mexicans and Hispanics in the USA 33…”
Section: Discussionsupporting
confidence: 89%
“…In each of these ethnic groups, cardiovascular disease and diabetes are the main causes of morbidity and mortality 1718 Data from the Suriname Health Study on pre-diabetes and diabetes showed a prevalence of 13% for diabetes overall and of 23.3% in the Hindustanis 1920 The MetS components described in this analysis indicated the highest median values for central obesity in the Amerindians and Hindustanis, the highest mean systolic blood pressure values in the Creoles and the mean values for blood glucose and blood lipids most approaching deviating values in the Javanese and Hindustanis 19.…”
Section: Introductionmentioning
confidence: 99%
“…Both diabetes mellitus and hypertension were less prevalent than the national average for women (resp. 13% and 20%) [22][23]. The relatively high prevalence of Me TS found in both study groups coupled with the relatively low prevalence of hypertension and diabetes mellitus could be an indication that both these subpopulations are in epidemiological transition [2,24], though at different stages.…”
Section: Discussionmentioning
confidence: 80%
“…Another limitation is the inclusion of only a small number of people of Amerindian descent. Ethnic differences in risk factors for diabetes have been shown in neighbouring Suriname [16] with an absence of an association with BMI in Amerindians. Other studies have shown a lower rate of diabetes in Amerindians in remote villages [17] but higher rates associated with increased biological risk factors in urban settings [18].…”
Section: Discussionmentioning
confidence: 99%